Possible effects of melatonin on thymus gland after pinealectomy in rats - Öner, H; Kus, I; Öner, J; Ögeturk, M; Ozan, E; Ayar, A (Maghira & Maas Publications, 2004)
OBJECTIVES: The purpose of this study was to investigate the effects of pinealectomy and pinealectomy plus melatonin administration on thymus weight and histology in adult Wistar-albino rats. METHODS: The animals were divided into three groups. Group I and Group II were designated as control (sham-pinealectomized) and pinealectomized rats, respectively. They received 10% ethanol (0.1 ml per day s.c.) alone. The rats in Group III were pinealectomized and daily injected with melatonin (3 mg/kg/0.1 ml 10% ethanol per day s.c.) commencing on the day seven after surgical operation. Injections were applied for two months. RESULTS: The thymus atrophied and its weight decreased after pinealectomy (p<0.001). The cortico-medullary boundary could not be distinguished and in the thymus induced a loss of lymphoid elements, increased number of phagocytic macrophages and enlarged blood vessels. Melatonin prevented the thymic involution. CONCLUSIONS: These results suggest that pinealectomy decreases thymus weight and that long-term administration of melatonin restores thymus weight to normal levels.
Keywords: melatonin; pinealectomy; thymus